2022
DOI: 10.1186/s12871-022-01842-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation for preoxygenation before general anesthesia: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background and objectives Preoxygenation is crucial for providing sufficient oxygen reservoir to a patient before intubation and enables the extension of the period between breathing termination and critical desaturation (safe apnoea time). Conventionally, face mask ventilation is used for preoxygenation. Non-invasive ventilation is a new preoxygenation method. The study objective was to compare the outcomes of non-invasive ventilation and face mask ventilation for preoxygenation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…Using CPAP or NIV during pre‐oxygenation and induction of anaesthesia will be more advantageous for certain patients, especially for obese patients, 20 and in patients with acute hypoxemic respiratory failure 21 . The benefits of PEEP in the context of protective intraoperative ventilation have a strong evidence base, 22 but the level of PEEP must not cause an increase in driving pressure 23 …”
Section: Discussionmentioning
confidence: 99%
“…Using CPAP or NIV during pre‐oxygenation and induction of anaesthesia will be more advantageous for certain patients, especially for obese patients, 20 and in patients with acute hypoxemic respiratory failure 21 . The benefits of PEEP in the context of protective intraoperative ventilation have a strong evidence base, 22 but the level of PEEP must not cause an increase in driving pressure 23 …”
Section: Discussionmentioning
confidence: 99%
“…The use of NIV to preoxygenate pregnant women has not yet been studied, but extrapolation from obese and ICU patients may provide useful insights. NIV is superior to facemask preoxygenation in both obese and hypoxic intensive care patients, but increases the risk of gastric distension and patient discomfort (20,21). However a small study in nonobstetric patients found no gastric insufflation using NIV with peak inspiratory pressures (PIP) of <20 cmH 2 O (22).…”
Section: Nivmentioning
confidence: 99%
“…For agitated patients, consider sedation or induction agents. During laryngoscopy, high-flow oxygen maintains airflow from the pharynx to the lungs [18].…”
Section: Pre Intubation Optimisation Of Oxygenationmentioning
confidence: 99%